Implementasi Kebijakan Sistem Zonasi Dalam Penerimaan Peserta Didik Baru Di Sekolah Menegah Atas Negeri 1 Sirenja Kabupaten Donggala - Fildayana, Fildayana; Kurnia, Intam; Mayusa, Askar (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
The purpose of this study is the Achievement of Equitable Distribution of Education Quality Through the Implementation of Zoning System Policy in the Admission of New Students at State High School 1 Sirenja, Donggala Regency by using the Policy Implementation Model proposed by Van Mette Van Horn, namely Standards, Objectives and Policy Objectives, Resources, Characteristics of Implementing Agents, Attitudes or Trends (Dispotition) implementers, Inter-organizational communication and implementation activities, Economic, social and political environment. This type of research is Descriptive research and the basis of the research used is qualitative. The information was determined by Purposive Sampling with a total of 7 informants. The data collection technique used is Observation. In-depth interviews of informants and documentation for data collection are needed in the form of primary and secondary data. Data analysis carried out by Data Reduction, Data Model (data display), Conclusion: Pulling/Verifying. Checking the validity of the data using Source Triangulation. The Implementation of the Zoning System Policy in the Admission of New Students at State High School 1 Sirenja, Donggala Regency has not been running optimally. This is proven that there is still a serious problem. Starting from, the school makes its own internal policy and does not implement zoning strictly and still accepts students outside the zoning. As well as the lack of information known by the public about the zoning system. This reflects the inconsistency of resources to the zoning system policy.